Crystallization Tendency of Pharmaceutical Glasses: Relevance to Compound Properties, Impact of Formulation Process, and Implications for Design of Amorphous Solid Dispersions - Kohsaku Kawakami (Pharmaceutics, 2019)
Amorphous solid dispersions (ASDs) are important formulation strategies for improving the dissolution process and oral bioavailability of poorly soluble drugs. Physical stability of a candidate drug must be clearly understood to design ASDs with superior properties. The crystallization tendency of small organics is frequently estimated by applying rapid cooling or a cooling/reheating cycle to their melt using differential scanning calorimetry. The crystallization tendency determined in this way does not directly correlate with the physical stability during isothermal storage, which is of great interest to pharmaceutical researchers. Nevertheless, it provides important insights into strategy for the formulation design and the crystallization mechanism of the drug molecules. The initiation time for isothermal crystallization can be explained using the ratio of the glass transition and storage temperatures (Tg/T). Although some formulation processes such as milling and compaction can enhance nucleation, the Tg/T ratio still works for roughly predicting the crystallization behavior. Thus, design of accelerated physical stability test may be possible for ASDs. The crystallization tendency during the formulation process and the supersaturation ability of ASDs may also be related to the crystallization tendency determined by thermal analysis. In this review, the assessment of the crystallization tendency of pharmaceutical glasses and its relevance to developmental studies of ASDs are discussed.